2011
DOI: 10.1002/bies.201100100
|View full text |Cite
|
Sign up to set email alerts
|

From transporter to transceptor: Signaling from transporters provokes re‐evaluation of complex trafficking and regulatory controls

Abstract: When cells are starved of their substrate, many nutrient transporters are induced. These undergo rapid endocytosis and redirection of their intracellular trafficking when their substrate becomes available again. The discovery that some of these transporters also act as receptors, or transceptors, suggests that at least part of the sophisticated controls governing the trafficking of these proteins has to do with their signaling function rather than with control of transport. In yeast, the general amino acid per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 90 publications
(129 reference statements)
2
33
1
Order By: Relevance
“…The Gap1 permease is reported to activate protein kinase A (PKA), a property not shared by Can1 (38,39), and this kinase might thus catalyze subtle phosphorylation of the Bul proteins not visible in our experiments. Alternatively, PKA could modulate yet another protein modulating the function of the Bul proteins.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The Gap1 permease is reported to activate protein kinase A (PKA), a property not shared by Can1 (38,39), and this kinase might thus catalyze subtle phosphorylation of the Bul proteins not visible in our experiments. Alternatively, PKA could modulate yet another protein modulating the function of the Bul proteins.…”
Section: Discussionmentioning
confidence: 77%
“…Downregulation of Gap1 by external (and internal) amino acids is thus part of a mechanism allowing cells to adjust their yAAP repertoires according to the external concentration of amino acids. Downregulation of Gap1 when amino acids are abundant could also avoid detrimental hyperactivation of PKA in cells growing on a poor nitrogen source, as Gap1 is reported to activate this kinase (38,39). Regarding Can1, we have observed that its downregulation by Arg is not as complete/efficient as that of Gap1.…”
Section: Discussionmentioning
confidence: 81%
“…The difference between a transceptor and a pure receptor being that the transceptor can also transports the ligand into the cell. In recent years, evidence for transporters functioning as transceptors has been obtained in several eukaryotic systems (67). Interestingly in yeast, the Pho84 phosphate carrier that is considered as an essential component of the Pi-sensing system was characterized as a Pi transceptor (40).…”
Section: Discussionmentioning
confidence: 99%
“…A 'transceptor' is a transporter that also functions as a receptor for signal transduction [131]. This 'transceptor' concept is significant as it shifts the model of regulation of transporters to include the regulation of the sensing as well as the transport of small molecules.…”
Section: Transporters Functioning As Receptors -'Transceptors'mentioning
confidence: 99%